2023
DOI: 10.1101/2023.02.06.527295
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comprehensivein vivoscreen of yeast farnesyltransferase activity reveals broad reactivity across a majority of CXXX sequences

Abstract: The basis for the current understanding of farnesyltransferase (FTase) specificity was pioneered through investigations of reporters like Ras and Ras-related proteins that possess a C-terminal CaaX motif that consists of 4 amino acid residues: Cysteine – aliphatic1– aliphatic2– variable (X). These studies led to the finding that proteins possessing the CaaX motif are subject to a 3-step post-translational modification pathway involving farnesylation, proteolysis, and carboxylmethylation. However, emerging evid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Yeast expressing Ydj1 with prenylation-only sequences (CASQ and CAHQ) supported the most robust thermotolerance; these sequences were derived from yeast Ydj1 and human DNAJA2, respectively. The prenylation-only status of CAHQ was previously based on homology and prediction algorithms (Hildebrandt et al, 2016b; Kim et al, 2023) and is confirmed here by the observation that CAHQ supports thermotolerance similar to CASQ and is resistant to proteolysis by the CaaX proteases ( Supplemental Figure S3 ). Yeast expressing Ydj1 with canonical CaaX sequences (CVIA and CTLM) exhibited partial growth under this condition as has been previously observed (Hildebrandt et al, 2016b); these sequences were derived from yeast a -factor and Gγ Ste18, respectively.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Yeast expressing Ydj1 with prenylation-only sequences (CASQ and CAHQ) supported the most robust thermotolerance; these sequences were derived from yeast Ydj1 and human DNAJA2, respectively. The prenylation-only status of CAHQ was previously based on homology and prediction algorithms (Hildebrandt et al, 2016b; Kim et al, 2023) and is confirmed here by the observation that CAHQ supports thermotolerance similar to CASQ and is resistant to proteolysis by the CaaX proteases ( Supplemental Figure S3 ). Yeast expressing Ydj1 with canonical CaaX sequences (CVIA and CTLM) exhibited partial growth under this condition as has been previously observed (Hildebrandt et al, 2016b); these sequences were derived from yeast a -factor and Gγ Ste18, respectively.…”
Section: Resultssupporting
confidence: 83%
“…The ability of Sc FTase to modify the non-canonical CaaX sequence associated with Ydj1 (CASQ) and other non-canonical sequences has been reported (Berger et al, 2018; Hildebrandt et al, 2016b; Kim et al, 2023; Ravishankar et al, 2023). The complementation studies described above indicate that Hs FTase can also modify the Ydj1 CASQ sequence (see Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations